Association Between Acute Inflammatory Response and Infarct Size in Stemi Patients Undergoing Primary PCI - Morariu Mirabela; Márton Emese; Mester András; Rațiu Mihaela; Benedek Imre (Journal of Cardiovascular Emergencies, 2018)
Background: The inflammatory response of the immune system plays a major role in the period following an acute myocardial infarction (MI), as it coordinates the formation of the fibrous scar tissue that replaces the infarcted myocardial cells and ultimately leads to healing and remodeling of the affected zone. Along with other pro- and anti-inflammatory cytokines and acute phase proteins, interleukin-6 (IL-6) and C-reactive protein (CRP) are associated with the extent of the infarct size (IS) and may serve as predictors for remodeling and adverse left ventricular (LV) function. Material and methods: A single-center, non-randomized, observational prospective study was conducted, which included 75 patients with primary revascularized ST-elevation myocardial infarction (STEMI). High-sensitivity CRP (hs-CRP) serum levels were determined on day 1 and day 5 following the acute event. IL-6 was also determined on day 1. All patients underwent cardiac magnetic resonance imaging (CMR) at 1-month follow-up with determination of LV function and quantification of the scar tissue using late gadolinium enhancement imaging. The patients were divided into 2 groups based on baseline hs-CRP values. Results: Patients with higher baseline hs-CRP levels presented significantly higher infarct size (p = 0.0003), higher transmural extent (p <0.0001), lower LV ejection fraction (p = 0.0024), end-systolic (p = 0.0021) and end-diastolic (p = 0.0065) volumes. Small IS (<10%) recorded the lowest levels of hs-CRP, while IS >20% presented the highest levels of hs-CRP, at baseline and day 5 (p = 0.4 and 0.001). IL-6 levels were also associated with the magnitude of infarct scar: 2.17 pg/mL for IS <10%, 15.52 pg/mL for IS between 10% and 20%, and 24.52 pg/mL for IS >20%, p = 0.002. Conclusion: hs-CRP and IL-6 serum levels following an MI are correlated with IS, transmurality extent of the scar tissue, as well as with altered systolic and diastolic LV function determined by CMR at 1-month follow-up.